Optimization of Rose Extraction Process by Orthogonal Design - Dan Chen, Xiao Cao, Heng Li, Limin Wu, Xin Zhang (Forest Chemicals Review, 2021)
To optimize the rose extraction process and evaluate the antioxidant properties of the extracts. The contents of gallic acid and rutin in rose extracts were used as indicators. According to the results of single-factor evaluation of the crushing degree of rose during extraction, extraction method, solid-liquid ratio of extraction and ethanol concentration. The three-factor and three-level L9 (33) orthogonal design optimized extraction scheme was established. The factor levels were as follows: solid-liquid ratio (1:8, 1:10, 1:12); Ethanol concentration of extractant (50%, 80%, 100%); Extraction method (ultrasonic treatment with ice for 30min, 3 times; Ultrasonic treatment with ice for 1h and 3 times; Reflux in water bath for 1h, 3 times); The DPPH in vitro antioxidant test was applied to compare the antioxidant capacity of the optimized extract and rose water extract. The best extraction scheme of rose was as follows: the ratio of solid to liquid was 1:10, the concentration of ethanol was 80%, and the extraction method was ultrasonic for 1 hour and repeated three times. In the antioxidant experiment, it can be found that the antioxidant capacity of the extract is significantly higher than that of the rose water extract. The optimized rose extract has a significantly higher antioxidant capacity than the rose water extract. The establishment of the extraction method significantly improves the utilization rate of antioxidant components in roses. It not only helps to improve the utilization rate of roses and avoids waste, but also helps the development and utilization of rose-related health products.